HAFF DISEASE IN BRAZIL: CLINICAL, EPIDEMIOLOGICAL AND NOTIFIABLE FINDINGS IN VIEW OF THE IMPORTANCE OF THE VETERINARIAN IN PUBLIC HEALTH - Patrícia Costa Gonçalves Alves, Erika; Francisca Lima Soares, Jeovannia; de Deus Ferreira Alves, Amanda (Journal of Interdisciplinary Debates, 2025)
This article aims to deepen the understanding of Haff’s disease in the Brazilian context, high- lighting the importance of veterinarians in preventive and educational actions for the popula- tion. The research was based on scientific articles, specialized literature, official documents, and other relevant sources. Haff’s disease, or Haff’s syndrome, is characterized as a rare and potentially severe clinical condition, commonly associated with the consumption of fish, mollusks, and crustaceans. This syndrome, whose etiology remains unknown, causes rhabdomy olysis and can progress rapidly, leading to acute kidney failure in some cases. In Brazil, outbreaks have been recorded in various regions, emphasizing the need for epidemiological surveillance and intervention by health professionals. Over the past four years (2021 to 2024), 537 cases compatible with Haff’s disease have been identified in Brazil, with the highest incidence in the North and Northeast of the country. Of these cases, at least 10 resulted in death. In this context, veterinarians emerge as key figures in combating zoonoses, with roles in food inspection, sanitary and epidemiological surveillance, as well as food quality control. It is concluded that veterinarians play an essential role in identifying potential sources of contami- nation and guiding the safe consumption of animal-derived products, establishing themselves as indispensable agents for public health and the prevention of this disease.